Difficulties in differential diagnosis of atopic dermatitis in children - L.V. Besh; O.I. Matsyura; Kh.O. Lishchuck-Yakymovych; R.M. Pukaliak; S.V. Lugovskyi (Zaslavsky O.Yu., 2018)
The article presents a literature review and our own experience in differential diagnosis of atopic dermatitis. Diagnostic difficulties were described on the example of the analysis of the observation of 57 children with atopic dermatitis (aged 1-5 years), and a diagnostic algorithm was offered that included three stages: clinical (detailed collection of complaints and anamnestic data), laboratory (general blood test, biochemical and coprological examination, determination of total IgE and specific IgE to gluten, and different milk fractions, serological biomarkers of celiac disease) and instrumental (skin test at the time of achieving the disease control and, if necessary, endoscopy with subsequent histological examination of biopsy specimen of the small intestinal mucosa). Patients' observation was conducted in the Lviv Municipal Children's Allergology Center at the premises of the Non-Profit Commercial Enterprise "Lviv Municipal Children's Clinical Hospital". Children were examined at baseline and dynamically after 1, 2, and 3 months. Treatment effectiveness was evaluated based on the clinical symptoms, the nature and prevalence of rash, and severity of itching. The results of the study showed that in the study group, the following causes of resistance to treatment were detected in children with atopic dermatitis: 36.84 % - comorbid allergic diseases (71.43 % with uncontrolled course); 24.56 % - food allergy: 12.28 % - allergy to cow's milk protein; 7.02 % - lactase insufficiency; 7.02 % - helminthiasis; 5.25 % - streptodermia; 3.51 % - allergy to gluten; 3.51 % - celiac disease; 3.51 % - scabies; 1.75 % - hypersensitivity to food additives (E102), and in 3.51 % of children, the cause was not identified (further research is being carried out). The need for an individual approach to the laboratory and instrumental algorithm for the diagnosis of atopic dermatitis has been described, and the results of a particular approach to diagnosis have been shown.